Meningkatkan Kesadaran Hukum Masyarakat Tentang Bahaya Narkotika di Era Digitalisasi di Desa Kawahmanuk Kecamatan Darma Kabupaten Kuningan - Hidayat, Sarip; Adhyaksa, Gios; Andriyani, Yani; Apriyani, Pipin; Maulani, Sri; Romli, Muhammad; Trimelawati, Reni (Jurnal Pengabdian Siliwangi, 2024)
AbstractNarcotics are one of the problems faced by society, and must be resolved by the community itself as a form of enforcement of the occurrence of circulation, abuse and drug addicts, especially with the development of technology today, it is easy to circulate narcotics through social media, there are 27 (twenty seven) Narcotics Crime cases in Kuningan Regency based on the Case Tracking Information System ( SIPP) of the Kuningan District Court, even some of the perpetrators of abuse and addicts are children. Implementation Method Audience of the community service team with the Kawahmanuk village government holding a meeting to determine the agenda for implementing community service, implementation through counseling and reports and evaluations is the creation of articles and published in reputable national journals. Results and Discussion of community service to increase legal awareness in society there must be a desire from the community so that there is no abuse and addiction to narcotics through prevention such as socialization of the dangers of narcotics, Therefore proactive steps can be taken through: first, the family environment; second, the residential environment, and third, the work environment. So if this is implemented then abuse and addiction to narcotics can be prevented, with this digitalization is one form of manifestation in enforcing the law on Narcotics Crimes whose circulation through social media will be easy to prosecute.